2019
DOI: 10.1021/acs.chemrev.9b00472
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Based Vaccines: Current Progress and Future Challenges

Abstract: Vaccines have had a profound impact on the management and prevention of infectious disease. In addition, the development of vaccines against chronic diseases has attracted considerable interest as an approach to prevent, rather than treat, conditions such as cancer, Alzheimer's disease, and others. Subunit vaccines consist of nongenetic components of the infectious agent or disease-related epitope. In this Review, we discuss peptide-based vaccines and their potential in three therapeutic areas: infectious dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
370
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 425 publications
(409 citation statements)
references
References 176 publications
(286 reference statements)
2
370
0
Order By: Relevance
“…While the studied population size needs to be increased, we found that all the women who had developed a high-grade cervical lesion caused by HPV16 failed to produce anti-L1FG/HPV16 antibodies. These ndings could have obvious implications for the development of an L1 polycyclic peptide or a new molecular scaffold for peptides that could be an attractive perspective for ELISA testing and a cyclic peptide-based vaccine [33,50].…”
Section: Resultsmentioning
confidence: 99%
“…While the studied population size needs to be increased, we found that all the women who had developed a high-grade cervical lesion caused by HPV16 failed to produce anti-L1FG/HPV16 antibodies. These ndings could have obvious implications for the development of an L1 polycyclic peptide or a new molecular scaffold for peptides that could be an attractive perspective for ELISA testing and a cyclic peptide-based vaccine [33,50].…”
Section: Resultsmentioning
confidence: 99%
“…Rather than using the whole or a split fragment of the virus as the vaccine, antigenic proteins (or peptides) of the virus can be generated using recombinant technology in the laboratory instead ( 98 ). This is the most popular approach in the SARS-CoV-2 vaccine development field, with 50 protein/peptide constructs in preclinical trials and 8 that have entered clinical trials ( Table 1 ).…”
Section: Different Vaccine Approaches Used In Covid-19 Vaccine Develomentioning
confidence: 99%
“…Peptide-based vaccines are generally designed based on the minimal peptide epitope that is still able to trigger the desired immunity. Peptide-based vaccines can suffer the disadvantage of being sensitive to any mutation within the selected epitopes and too genetically constrained due to the specificity of the T-cell receptor (TCR) [38]. Further, low immunogenicity is a typical weakness of peptide-based vaccines; however, it can be minimized through the development of better adjuvant-based delivery systems.…”
Section: Introductionmentioning
confidence: 99%